Performance Evaluation In Hospitals Of Lorestan University Of Medical Sciences Using Pabon-Lasso Model - Zahra Kavosi; Sahar Goodarzi; Abdollah Almasiankia (Tehran University of Medical Sciences, 2013)
Background and Aim: Assessment of hospital performance increases responsiveness and efficiency of limited resources. One of the most useful models of hospital performance assessment is Pabon-Lasso, a graphical model that determines the relative performance of hospitals using three indicators: Bed Occupancy Rate Bed Turnover and Average Length of Stay. The present study aims to compare the performance of Lorestan University of Medical Sciences (LUMS) hospitals using the above-mentioned tools. Materials and Methods: In this descriptive cross-sectional study, fourteen LUMS hospitals were selected through census. The data-gathering instrument was the standard data form verified by the Ministry of Health and Medical Education. Bed Occupancy Rate, Average Length of Stay, and Bed Turnover Rate were calculated and Pabon-Lasso graph was drawn using SPSS 15. Results: The average length of stay, bed occupancy, and bed turnover rates turned out to be 3/21 days, 53/07% and 95/54, respectively. Five hospitals were in Zone III, indicating a satisfactory level of efficiency. Four hospitals demonstrated inefficiency and underutilization of resources by falling into Zone I. Three hospitals were placed n Zone II. And two hospitals were in Zone IV. Conclusion: Among 14 studied hospitals, just 5 were considered as efficient. Therefore, it is necessary that policy-makers develop solutions to improve the performance of other hospitals and distribute health resources appropriately.